Mistletoe lectin-I augments antiproliferative effects of the PPARγ agonist rosiglitazone on human malignant melanoma cells - Freudlsperger, Christian; Dahl, Anka; Hoffmann, Jürgen; Reinert, Siegmar; Schumacher, Udo (Phytotherapy research, 2010)
As malignant melanoma cells are highly resistant to conventional chemotherapy, survival rates after tumor spread remain poor and hence there is an urgent need for new therapeutic options. For both mistletoe lectin-I (ML-I) and the thiazolidinediones as synthetic ligands of the peroxisome proliferator-activated receptor γ (PPARγ) an antiproliferative effect on malignant melanoma cells has previously been shown. Hence, the aim of this study was to investigate whether the combination of ML-I and the PPARγ ligand rosiglitazone is more efficacious in the treatment of malignant melanoma cells than either agent alone. Proliferation of three human melanoma cell lines treated with ML-I, rosiglitazone and the combination of both was measured in a broad concentration range (0.0001-100 μg/mL) using the XTT cell proliferation assay. Combined application tremendously increased the antiproliferative effect on all three melanoma cell lines compared with single agent treatment. In comparison with the single use of rosiglitazone, the combination with ML-I significantly increased the inhibition of cell growth by 51-79% and in comparison with the single use of ML-I by 9-32%, respectively. In conclusion, this study shows that the combination of ML-I with rosiglitazone significantly augments their antiproliferative effect on malignant melanoma cells in comparison with their single agent application, which might be a promising tool for further therapeutic studies. Copyright © 2010 John Wiley & Sons, Ltd.